Crystallization and preliminary X-ray diffraction analysis of the TetR-family transcriptional repressor YhgD from Bacillus halodurans - Yeo, Hyun Ku (International Union of Crystallography, 2013)

(untitled)
YhgD is a member of the TetR-family transcription factors, which regulate genes encoding proteins involved in multidrug resistance, virulence, osmotic stress and pathogenicity. YhgD from the alkaliphilic bacterium Bacillus halodurans was cloned and overexpressed in Escherichia coli. YhgD (Bh2145) from B. halodurans is composed of 193 amino-acid residues with a molecular mass of 21 853 Da. YhgD was crystallized at 296 K using ethylene glycol as a precipitant by the sitting-drop vapour-diffusion method. The crystal diffracted to 1.9 Å resolution and belonged to the apparent triclinic space group P1, with unit-cell parameters a = 37.22, b = 47.85, c = 54.15 Å, α = 92.75, β = 107.9, γ = 90.27°. The asymmetric unit is likely to contain two molecules of monomeric YhgD, giving a crystal volume per mass (V (M)) of 2.05 Å(3) Da(−1) and a solvent content of 40.2%.